Thermodynamic performance analysis of over-expansion stroke and late inlet valve close on HCNG-SI engine - Tirkey J.V. (My University, 2025)
Low specific fuel consumption and low engine emission are the prime aims of engine design and simulation. Late inlet valve closing (LIVC) acts as over expansion stroke, and it increases the network output of power cycle of an engine. In unison, the effect of stroke/bore ratio on engine performance is also significant to evaluate. Concerning this, a computational analytical study of the power cycle has been incorporated to simulate a lean fuel-air equivalence of 0.75 comprising a mixture of 50% hydrogen and 50% natural gas (50HCNG) by mass. To analyse the performance, a thermodynamic computational model was used which comprise two-zone spherical geometry turbulent combustion, polynomial functioned fuel and species properties, and kinetically controlled CO and NO formation. In the computational program, differential equations were solved by Runge-Kutta method and iteration to the precise accuracy of the solution to species equilibrium equation by Newton-Raphson numerical technique. The numerical predictions include the validation of result, combustion duration (CD), indicated mean effective pressure (IMEP), peak pressure and temperature, efficiency, power, specific fuel consumption, and emission of CO and NO to change in stroke to diameter ratio and LIVC. Results conclude that there is a significant enhancement in indicated thermal efficiency (ITE) and reduction in specific fuel consumption and emissions using an over-expansion stroke attributable to LIVC at a different stroke to bore ratio. © 2018 Acta Press. All rights reserved.